(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The tender (auction) and also other procedures of offering public orders are taking place in non typical relations which have multilateral and eliminatory character. The organizator of procedures ordering doesn’t use any attributes of public power, acts on the base of civil principle equality of the parties. Traditional liability for damages of the ordering party for organizational faulties and other other measures connected with invalidity of final contract have been insufficient. In the second half of XX century under influence of the practise in some european countries were allowed more effective claims for making corrects used presently in the procedure due to eliminate immediately the faulties to not admmitte the conclusion non effecive contract and increase the damages. Those experiences are the base of council Directive 89/ 665/ ECC of 21 December 1989 on the coordination of the laws, regulations and administrative provisions relating to the application of review procedures to award of public supply and public works contracts, which contributed only partly harmonization of european legal orders. Because of it this Directive was amended by Directive 2007/66/EC of the European Parliament and the Council of 11 December 2007 amending the Council Directives 89/ 665/ ECC and 92/13/ECC with regard to imroving the effectiveness of review procedures concerning the award of public contracts. The period of implementation of it will expire 20 December 2009. To inculate this Directives regulations to the polish public orders law is necessary particularly: a) widdening the notion of legal interest what is the base for lodging appeal measures, b) rethinking once more the sense and function of initial signalling the faulties by the competitors making protest, c) reforming the procedure in the Domestic Appeal Chamber, d) extending the period and allowing electronic form for Appeal measures, e) justification of the court control of the decisions done by the Chamber and make possible those issues to appeal court decisions, f) introducing the sanctions of anullment the contract by authorised body instead of binding now santion absolute invalidity g) verification legal causes of contract ineffectiveness, h) increase the liability for damages the ordering party without the traditional condition of the fault, i) rethinking the additional preventive-disciplinary measures especially financial penalties. Beside those important improvings necessary is also to to become perfect some binding regulations due to increase the speed and effectiveness of examining appeal measures what sometimes obstruct possibility of conclusion final contract in the time of standstill. Necessary is especially rethinking the circumstances for preparation the appeal without obstruction of the cotract conclusion. In the case of anullment the protest as a preemption act of the complaint may be necessary improve new regulation to allow ordering party the correction of faulties before opening hearing in the Domestic Appeal Chamber, which can terminate the procedure in all cases of effective voluntary removal of faulties the law by the ordering party. Important are also regulations connected with the performance of decision done by Domestic Appeal Chamber especially those which allow compulsory enforcement this provisions.